Emic Definitions of Health and Illness in Rural Muslim and Christian Communities of Lanao del Norte - 0. TAN, BERNADETTE (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Selected predominantly Christian and predominantly Muslim rural communities in Lanao del Norte were surveyed to determine the rural folks definitions of health and illness. In-depth interviews guided by a structural interview schedule, were conducted among 401 respondents selected through stratified multi-stage random sampling. Two hundred fifty three (253) respondent were selected from three (Bacolod, Kapatagan, & Magsaysay) predominantly Christian communities (PCCS), and 148 from two (Balo-I & Pantao-Ragat) predominantly Muslim communities (PMCs). Majority of the respondents are mothers and housekeepers with household incomes below the poverty line identified by NEDA. Data reveals that the emic (culture-specific concepts) indicators for health identified by both PCC’s and PMC’s respondents generally correspond with medical science’s etic (pre-determined general concepts) indicators. Both sets of respondents emically defines health as composed of factors like positive behavior, positive psychological state & positive physical appearance. While illness is composed of factors like abnormal physical appearance, presence of symptoms and the like. There are some specific instances wherein the emic definition of respondents demote from the etic Some illness indicators of modern medicine like distended abdomen to indicate parasitic infection are considered by rural folks as without medical significance. Majority of the two types of communities (PCC’s-69%; PMC’s 71%) have the fatalistic attitude and belief that diseases could not be avoided. Findings of this research would be useful to the policy and decision-makers particularly the DOH and Local Government Units (GUs) in their intervention program for the maintenance and attainment of health of the populace.